2011
DOI: 10.1080/07448481.2010.546464
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of an Outdoor Residential Hall Smoking Policy in a California Public University: A Case Study

Abstract: The survey data and institutional comparisons played a key role in administrators' decision-making about campus smoking policy. Despite administrators' concerns about students' safety and freedom of choice, student-led advocacy was able to influence policy change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
6
1
1
Order By: Relevance
“…Indeed, it has been demonstrated that providing survey evidence of broad student support can be a decisive influence on the decision to implement controls on outdoor smoking (Garg et al, 2011). The sizable majority of students in support of outdoor smoking restrictions in the present study is higher than the level of support reported in some previous research (Loukas et al, 2006;Rigotti et al, 2003;Thompson et al, 2006).…”
Section: Implications For Policy Interventionscontrasting
confidence: 73%
See 1 more Smart Citation
“…Indeed, it has been demonstrated that providing survey evidence of broad student support can be a decisive influence on the decision to implement controls on outdoor smoking (Garg et al, 2011). The sizable majority of students in support of outdoor smoking restrictions in the present study is higher than the level of support reported in some previous research (Loukas et al, 2006;Rigotti et al, 2003;Thompson et al, 2006).…”
Section: Implications For Policy Interventionscontrasting
confidence: 73%
“…For example, the 2013 National College Health Assessment, which allowed participating institutions to use either Web or paper modes, reported a mean response rate of 18% for those institutions using Web administration (American College Health Association, 2013). Other recent tobacco-related survey studies have reported response rates between 19% and 31%, including even some cases where a gift or raffle entry has been offered to encourage response (Berg et al, 2011;Burns et al, 2013;Garg et al, 2011;Primack et al, 2013;Reed et al, 2007;Wolfson et al, 2009). More generally, these results may be indicative of the larger trend toward reduced survey participation that has been described by survey researchers in recent years (Kim et al, 2011).…”
Section: Study Limitations and Strengthsmentioning
confidence: 99%
“…Two studies [ 24 , 25 ] were excluded because these studies did not assess students’ tobacco use behavior. One study [ 26 ] was excluded because it was not quantitative. Five studies [ 17 19 , 27 , 28 ] were excluded because the studies focused on compliance to existing smoking policies and did not assess the impact of policies on behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The proportions of US students supporting such policies in 3 of the publications were 56%, 15 57.5% (control campus), 16 61.1% (intervention campus), 16 and 66%. 17 One US study, using a 1-7 scale of support, reported an average response of 4.57, on the supportive side of neutral. 18 Two 19,20 US studies stratified responses by smoking status, both reported higher levels of support among never smokers (3.08 19 on a 1-4 scale, with 4 being strongly agree and 43% 20 support) compared with current smokers (1.83 19 and 6.9% 20 ).…”
Section: Attitude Toward Smoke-free Policies Before Policymentioning
confidence: 99%